Advances in coconut micropropagation: prospects, constraints and way forward - Nikila, A; Renuka, R; Kumar, K K; Mohanalakshmi, M; Suresh, J; Thavaprakash, N (Plant Science Today, 2025)
Coconut is widely referred to as the "Tree of Life," holds immense value due to its versatility and significant role in numerous sectors including industry, agriculture, food and health. In recent years, a troubling decline in coconut production has been observed due to factors such as palm senility, pests, diseases and natural calamities which poses serious threats to industries and communities that rely highly on this crop thereby creating a gap between demand and supply. Addressing this gap requires innovative solutions and plant tissue culture techniques offer a promising path forward. Tissue culture techniques such as zygotic embryogenesis (mature embryo culture and sliced embryo culture), organogenesis (axillary bud culture and embryo derived shoot tip culture) and somatic embryogenesis have shown great potential for regenerating coconut plants. Axillary bud culture, offers a reliable alternative for producing elite plants with the added benefit of being free from the risk of somaclonal variation, while somatic embryogenesis, in particular has proven to be highly effective for producing large numbers of high-quality planting materials. However, each technique has its own share of shortcomings. Overcoming these challenges and closing the gap between demand and supply is critical for the mass production of elite coconut seedlings. This review explores the different micropropagation techniques, the hurdles facing coconut tissue culture and the potential for future breakthroughs.